The Influence of Welfare on the Performance of Early Childhood Education Teachers - Apriliani, Elina Intan; Sholihah, Aikah; Aisyah, Anisa Nur; Khasanah, Izzah Nur; Amelia, Via Anggi (CV. Creative Tugu Pena, 2023)
This research aims to investigate the relationship between welfare and performance of early childhood education teachers. It employs a qualitative approach, allowing for an in-depth understanding of teachers' experiences and perceptions regarding welfare and its influence on their performance. Research participants consist of teachers teaching at TK Ar Rahman Tasikmadu, Karanganyar, selected through purposive sampling techniques to obtain variations in their experiences and perspectives. Data are collected through in-depth interviews with teachers, focusing on the aspects of welfare they experience in the workplace and their perceptions of performance as a result of welfare. Data analysis utilizes a thematic analysis approach to identify thematic patterns in the interviews and understand the relationship between welfare and teacher performance. The results of this research indicate that teacher certification serves as an indicator of teacher welfare to enhance their performance in schools. This study provides a better understanding of how teacher welfare affects their performance at TK Ar Rahman Tasikmadu and offers insights for the development of policies and human resource management practices that support welfare and performance of teachers in early childhood education institutions. Keywords: Welfare, Teacher Performance, Early Childhood Education